Adolescent nicotine exposure transiently increases high-affinity nicotinic receptors and modulates inhibitory synaptic transmission in rat medial prefrontal cortex - Counotte, Danielle S. (2012)
Adolescence is a critical developmental period during which most adult smokers initiate their habit. Adolescents are more vulnerable than adults to nicotine’s long-term effects on addictive and cognitive behavior. We investigated whether adolescent nicotine exposure in rats modifies expression of nicotinic acetylcholine receptors (nAChRs) in medial prefrontal cortex (mPFC) in the short and/or long term, and whether this has functional consequences. Using receptor binding studies followed by immunoprecipitation of nAChR subunits, we showed that adolescent nicotine exposure, as compared with saline, caused an increase in mPFC nAChRs containing α4 or β2 subunits (24 and 18%, respectively) 24 h after the last injection. Nicotine exposure in adulthood had no such effect. This increase was transient and was not observed 5 wk following either adolescent or adult nicotine exposure. In line with increased nAChRs expression 1 d after adolescent nicotine exposure, we observed a 34% increase in amplitude of nicotine-induced spontaneous inhibitory postsynaptic currents in layer II/III mPFC pyramidal neurons. These effects were transient and specific, and observed only acutely after adolescent nicotine exposure, but not after 5 wk, and no changes were observed in adult-exposed animals. The acute nicotine-induced increase in α4β2-containing receptors in adolescents interferes with the normal developmental decrease (37%) of these receptors from early adolescence (postnatal day 34) to adulthood (postnatal day 104) in the mPFC. Together, this suggests that these receptors play a role in mediating the acute rewarding effects of nicotine and may underlie the increased sensitivity of adolescents to nicotine.